Sistem Pakar Mendiagnosa Penyakit Bipolar Dengan Menggunakan Metode Dempster Shafer - Melin Tri Ariska; Fuzy Yustika Manik; Magdalena Simanjuntak (CV. Ulil Albab Corp, 2022)
Bipolar is a mental disorder characterized by drastic changes in mood. People with this disorder can feel very happy and then turn into very sad. Based on data from the World Health Organization in 2017, there are about 45 million people worldwide who suffer from bipolar disorder. This disorder is one of the main causes of disability and death due to suicide worldwide. Therefore, it is necessary to design an expert system to assist patients in checking symptoms of the disease and preventing bipolar disorder by creating a system that can diagnose bipolar disease using the dempster method. shader. a mathematical theory that aims to prove based on belief function and plausible reasoning and a consultation test was carried out in this study by diagnosing the disease based on the symptoms experienced. is (P2), which is 0.80 or if it is used as a presentation, it is 80%.